A straightforward and "green" solvothermal synthesis of Al doped zinc oxide plasmonic nanocrystals and piezoresistive elastomer nanocomposite. Issue 78 (26th August 2015) - Šutka, Andris; Timusk, Martin; Döbelin, Nicola; Pärna, Rainer; Visnapuu, Meeri; Joost, Urmas; Käämbre, Tanel; Kisand, Vambola; Saal, Kristjan; Knite, Maris
<x xml:space="preserve">Abstract</x> Ethanol solvothermal method derives plasmonic Al doped ZnO nanocrystals suitable for advanced applications.